2021
DOI: 10.7717/peerj.11290
|View full text |Cite
|
Sign up to set email alerts
|

Taphonomy and taxonomy of a juvenile lambeosaurine (Ornithischia: Hadrosauridae) bonebed from the late Campanian Wapiti Formation of northwestern Alberta, Canada

Abstract: Hadrosaurid (duck-billed) dinosaur bonebeds are exceedingly prevalent in upper Cretaceous (Campanian–Maastrichtian) strata from the Midwest of North America (especially Alberta, Canada, and Montana, U.S.A) but are less frequently documented from more northern regions. The Wapiti Formation (Campanian–Maastrichtian) of northwestern Alberta is a largely untapped resource of terrestrial palaeontological information missing from southern Alberta due to the deposition of the marine Bearpaw Formation. In 2018, the Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 105 publications
(345 reference statements)
0
12
0
Order By: Relevance
“…Although smaller sized individuals can be subject to hydraulic sorting (Brown, Evans, Ryan, & Russell, 2013; Brown, Evans, Campione, et al, 2013), the results of the RMDQ autopodial element size‐frequency distribution (Figure 6) indicated that autopodial elements were present in excess and did not vary in their overall degree of completeness relative to long bones from the same population. This suggests that taphonomic biases had not contributed toward the absence of nestling‐sized long bones in the RMDQ sample, which were hydraulically equivalent to late juvenile‐adult autopodial elements, providing further evidence that segregation between nestling‐juvenile and adult hadrosaurids may have been a real biological signal (e.g., Holland et al, 2021; Lauters et al, 2008; Varricchio & Horner, 1993; Wosik et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although smaller sized individuals can be subject to hydraulic sorting (Brown, Evans, Ryan, & Russell, 2013; Brown, Evans, Campione, et al, 2013), the results of the RMDQ autopodial element size‐frequency distribution (Figure 6) indicated that autopodial elements were present in excess and did not vary in their overall degree of completeness relative to long bones from the same population. This suggests that taphonomic biases had not contributed toward the absence of nestling‐sized long bones in the RMDQ sample, which were hydraulically equivalent to late juvenile‐adult autopodial elements, providing further evidence that segregation between nestling‐juvenile and adult hadrosaurids may have been a real biological signal (e.g., Holland et al, 2021; Lauters et al, 2008; Varricchio & Horner, 1993; Wosik et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Hadrosaurid dinosaurs have been historically defined as being gregarious based on evidence of numerous bonebed accumulations (e.g., Christians, 1992; Colson et al, 2004; Horner et al, 2004; Lauters et al, 2008; Scherzer & Varricchio, 2010; Bell & Campione, 2014; Eberth et al, 2014; Hone et al, 2014; Evans et al, 2015, Woodward et al, 2015, Ullmann et al, 2017; Bell et al, 2018, Holland et al, 2021). However, before estimating the population dynamics of an extinct animal, the depositional origin of the sampled assemblage, including the manner of death, need to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Large ornithopod tracks from Tyrants Aisle are attributed to hadrosaurids, whose skeletal remains and tracks are ubiquitous throughout the Wapiti Formation [ 8 , 10 12 , 15 17 , 55 , 105 ]. Within Unit 4, a ‘mummified’ specimen of the saurolophine Edmontosaurus regalis (UALVP 53722) was found near Red Willow Falls, ~16km upstream from Tyrants Aisle [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal and other evidence, including rare nesting sites (e.g., [ 116 118 ]) and common hadrosaurid-dominated bonebeds (e.g., [ 20 , 25 , 119 123 ]) further indicate widespread herding behaviour among these dinosaurs. More specifically, hadrosaurid-dominated bonebeds are also known from the Wapiti Formation [ 8 , 55 ]. In this context, it is possible that the abundant hadrosaurid trackmakers at Tyrants Aisle were also engaging in gregarious behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation